Attitudes towards Statistics in Social Science Students: Operationalization and Measurement - Екатерина Алексеевна Орел; Татьяна Евгеньевна Хавенсон (Psychology. Journal of the Higher School of Economics, 2013)
This article examines the nature of statistical anxiety – a state that arises when learning statistics, undergoing assessment of statistics knowledge or discussion of statistical material. The vast majority of studies indicate a strong negative relationship between statistical anxiety and achievement in subjects of probabilistic and statistical cycle. The article reviews the history of research and approaches to “the attitude towards statistics” concept. The authors describe the experience of the Russian-language adaptation of a scale measuring the attitude towards statistics in social sciences students. The work was based on the SATS-36 scale (Schau, 2003). The adaptation process included several stages: 1) the primary translation from English into Russian; 2) 10 cognitive interviews with students to verify the translation; 3) expert assessment of the second version of the translation; 4) a pilot survey on a sample of 70 students of the Faculty of Applied Political Science and Sociology, HSE; 5) the main survey.The study was conducted on a sample of 253 students of three HSE faculties: Applied Political Science (N=88), Psychology (N=69) and Sociology (N=96). The factor structure of the questionnaire was explored, which resulted in the removal of the two statements that did not satisfy the empirical data collected. Reliability and validity of the questionnaire were confirmed: relatively high values of Cronbach's alpha suggest that the questions within each scale are measuring the same construct; at the same time, correlations with related constructs were low enough to confirm the existence of a separate "statistical anxiety" or "attitude towards statistics" construct. The resulting factors were slightly different from the original English version; however, they were more relevant to the Russian-speaking educational environment.